The Impact of English Language Proficiency on Interpersonal Interactions among Students from Different Nationalities in a Malaysian Public University - Sarwari, Abdul Qahar; Ainol Haryati, Ibrahim; Nor Ashikin, Abdul Aziz (Universiti Putra Malaysia Press, 2016)
English language is the main communicative means among local and international students of Malaysian universities. Thus, this study was carried out to evaluate the impact of English language proficiency (ELP) on interpersonal and intergroup interactions among students from different nationalities in a Malaysian public university. An embedded design of mixed methods with the predominant role of the quantitative method was applied to conduct this study. The quantitative method, with 220 participants from both local and international students, was used as the main method and interviews were carried out to enrich the data. The results of this study confirmed that ELP is among the main factors that affect the process of interactions among local and foreign students of Malaysian public universities. Based on the findings of this study, lack of ELP among both local and international students and their different accents and linguistic assumptions have negative impacts on the process of interactions among them.